2022
DOI: 10.18196/jai.v23i2.15462
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Baitul Maal Wat Tamwil Financing and Business Coaching on Business Development and Welfare Improvement of Micro Traders in Traditional Markets

Abstract: Research aims: This study aims to analyze the role of financing and business coaching in BMT (Baitul Maal Wat Tamwil). The role of financing and business coaching focused more on its impact on business development and improved welfare of BMT members who carried out financing. BMT members here were specifically from micro-enterprises by traditional market traders.Design/Methodology/Approach: Market traders used as objects were still micro-scaled in traditional markets in Purworejo Regency, Central Java. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…The result demonstrated that the governance in those activities has been carried out well and can encourage the social mobility of customers. Also, Darma and Handoyo (2022) argue that BMT has a key role in helping the welfare of its members through product financing and assistance for the success of its members' businesses.…”
Section: Corporate Governance and Its Principlesmentioning
confidence: 99%
“…The result demonstrated that the governance in those activities has been carried out well and can encourage the social mobility of customers. Also, Darma and Handoyo (2022) argue that BMT has a key role in helping the welfare of its members through product financing and assistance for the success of its members' businesses.…”
Section: Corporate Governance and Its Principlesmentioning
confidence: 99%